Factors Affecting Evidence-Based Practices in Foreign Rehabilitation Therapists'Service and Its Implications for China - Yali WANG; Keli MU (康复学报)
Evidence based practice (EBP), emerged at the turn of 70s and 80s in the 20th century, has been developed rapidly and been applied to medical rehabilitation field and other health care professions such as occupational therapy and physical therapy. Development and application of EBP, however, is still hindered by various internal and external factors. After reviewing pertinent previous literature, this paper systematically examined the factors that influence the EBP in foreign rehabilitation therapists'service, such as organizational environment, education and training of rehabilitation professionals, therapists'perception, and professionals'practice setting and time, etc., discussed the implications to EBP in rehabilitation therapists'service in China and offered suggestions to the further development in current China.